Langman's medical embryology - Sadler, T. W. (Thomas W.) (Wolter Kluwer, 2015)
Offering exceptional full color diagrams and clinical images, Langman's Medical Embryology, 13e helps medical, nursing, and health professions students develop a basic understanding of embryology and its clinical relevance. Concise chapter summaries, captivating clinical correlates boxes, clinical problems, and a clear, concise writing style make the subject matter accessible to students and relevant to instructors.